Respuesta :
-4c - 11 = 4c +21 add 4c to both sides
-4c - 11 + 4c = 4c + 21 + 4c simplify
- 11 = 8c + 21 subtract 21 from both sides
- 11 - 21 = 8c + 21 - 21 simplify
- 32 = 8c divide both sides by 8
c = - 4
That's it
-4c - 11 + 4c = 4c + 21 + 4c simplify
- 11 = 8c + 21 subtract 21 from both sides
- 11 - 21 = 8c + 21 - 21 simplify
- 32 = 8c divide both sides by 8
c = - 4
That's it
I hope you got the idea
Move all terms containing C to the left side of the equation. -8c-11=21
Move all terms not containing C to the right side of the equation. -8c=32
Divide each term by -8 and simplify.
32/8 equals -4
C=-4
Move all terms not containing C to the right side of the equation. -8c=32
Divide each term by -8 and simplify.
32/8 equals -4
C=-4